Synthesis, structure, and reactivity of (η5:η1-C5Me4(CH2)2NMe2)Re(CO)2. Electron transfer behavior of a nitrosyl derivative - Godoy, Fernando (2014)
The UV irradiation of a hexane solution of the complex (h5 -C5Me4(CH2)2NMe2)Re(CO)3 (1) afforded the chelated species (h5 :h1 -C5Me4(CH2)2NMe2)Re(CO)2 (2). The molecular structure of 2 has been determined by X-ray crystallography. The reaction of 2 with two-electron donor ligands yields (h5 - C5Me4(CH2)2NMe2)Re(CO)2(L) (1, L ¼ CO; 3, L ¼ PMe3). The chelated species 2 also reacts with MeOTf, HBF4, and I2 to form the cationic compounds trans-[(h5 -C5Me4(CH2)2NMe2)Re(CO)2X]þ ([4]D, X ¼ Me; [5]D, X ¼ H; [6]D, X ¼ I). The trans stereochemistry of 4e6 have been assigned on the basis of n(CO) IR intensities and 13C NMR spectroscopy. Also, complex 2 reacts with nitrosyl tetrafluoroborate to yield [(h5 - C5Me4(CH2)2NMe2NO)Re(CO)2(NO)]BF4 ([7]2D). The redox behavior of the {ReNO}6 complex [7]2D was studied and the products obtained after two-electron reduction were characterized by IR. DFT calculations were done to optimize the structure of [7]2D and to study the effect of the sidearm coordination on the electronic structure of a cyclopentadienyl {ReNO}8 complex.